Does it matter how aggregates are measured? The case of monetary transmission mechanisms in the euro area - Andreas Beyer; Katarina Juselius (European Central Bank (ECB), 2010)
Beyer, Doornik and Hendry (2000, 2001) show analytically that three out of four aggregation methods yield problematic results when exchange rate shifts induce relative-price changes between individual countries and found the least problematic method to be the variable weight method of growth rates. This papers shows, however, that the latter is sensitive to the choice of base year when based on real GDP weights whereas not on nominal GDP weights. A comparison of aggregates calculated with different methods shows that the differences are tiny in absolute value but highly persistent. To investigate the impact on the cointegration properties in empirical modelling, the monetary model in Coenen & Vega (2001) based on fixed weights was re-estimated using flexible real and nominal GDP weights. In general, the results remained reasonably robust to the choice of aggregation method.
Keywords: C32; C42; E41; 330; Aggregation; cointegration; Eurowide money demand; Flexible weights; Aggregation; Wirtschaftsindikator; Geldpolitische Transmission; Geldnachfrage; Kointegration; Eurozone; EU-Staaten